Willingness to Communicate in English of Non-English Major University Students in Indonesia - Subekti, Adaninggar Septi (Lingua Cultura, 2019)
This research was conducted to investigate the willingness to communicate (WTC) of Indonesian learners of English as aÂ second language (L2) at the university level. It was conducted based on several rationales. WTC in L2 was often regarded asÂ the primary goal of language instructions, and there might be various factors influencing WTC in L2 and the two so-calledÂ strongest factors, namely learnersâ€™ perceived communication competence and communication apprehension, need to beÂ investigated further to find out the degree to which they affected learnersâ€™ WTC. Besides, Indonesian learnersâ€™ low frequencyÂ of English use outside classroom contexts might lead them to be unwilling to make actual communication in English. ThroughÂ probability random sampling, a total of 276 non-English major university students participated in the study, the data of whichÂ were analyzed using descriptive statistics and inferential statistics, correlation and regression, in SPSS 21. This researchÂ finds that learners have reported a high level of WTC, their perceived communication competence is found to be a strongÂ predictor of learnersâ€™ WTC, communication apprehension is found to be correlated with WTC in just a moderate level, andÂ despite expertsâ€™ supports on the importance of WTC in L2 learning, it surprisingly cannot predict learnersâ€™ L2 achievement. Â